Colored aluminum anode oxide film and preparation method thereof

Azo dyes were synthesized in situ in the pores of aluminum oxide films through electrochemical polishing and anodizing processes, which solved the problems of insufficient color stability and weather resistance of existing aluminum anodized films, and achieved a uniform and firm coloring effect and good salt spray resistance.

CN120818873APending Publication Date: 2025-10-21SHENZHEN JINMING AVIATION TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510958976.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-11
Publication Date
2025-10-21

AI Technical Summary

Technical Problem

The existing colored aluminum anodized films lack sufficient color stability and weather resistance.

Method used

A red azo dye was synthesized in situ in the pores of a porous oxide film by using electrochemical polishing and anodizing processes and the azo reaction between diazonium salt and sulfonic acid benzene. Combined with sulfonic acid-modified alendronic acid and azo precursors with specific structures, a uniform and firm colored aluminum oxide film was formed.

Benefits of technology

It improves the coloring effect of aluminum oxide film, ensures color uniformity and salt spray resistance, and enhances the weather resistance of film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120818873A_ABST
    Figure CN120818873A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of aluminum alloy materials, and particularly relates to a colored aluminum anode oxide film and a preparation method thereof. Aluminum is sequentially subjected to electrochemical polishing and anodic oxidation to obtain an aluminum anodic oxide film, then the aluminum anodic oxide film is immersed in an azo precursor solution, and a red azo dye is synthesized in situ in pores of the porous oxide film through an azo reaction between diazonium salt and benzene sulfonate, so that coloring of the aluminum oxide film is completed. By synthesizing sulfonic acid modified alendronate and compounding the sulfonic acid modified alendronate to form the electrochemical polishing solution, the electrochemical polishing quality of the surface of an aluminum sheet can be effectively improved. An electrolyte additive with phosphate groups, carboxyl groups and alcohol amino groups at the same time is used for anodic oxidation, a porous oxidation film with the appropriate pore size is formed, finally, an azo precursor of a specific structure is screened, loading fixation of azo dye on the porous film is further improved by means of sulfonic acid groups on azo molecules, and the stability of the anode is improved. And the aluminum oxide film with a good coloring effect is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of aluminum alloy materials, and specifically relates to a colored aluminum anodized film and a preparation method thereof. Background Art

[0002] Aluminum is a lightweight metal with advantages such as light weight, corrosion resistance, good ductility, and easy processing and forming. It is widely used in packaging, construction, and arts and crafts. In dry air, a dense oxide film of a certain thickness forms on the surface of aluminum, protecting it from further oxidation. However, this natural oxide film does not meet the protective properties required of aluminum. Therefore, to further improve the surface properties of aluminum, surface treatment is usually required. Aluminum and its alloys are anodized in an electrolyte to form a porous oxide film on the surface, known as anodized aluminum oxide film, or AAO film. This film has excellent corrosion and wear resistance. Chemical dyeing or secondary electrolytic coloring can produce an AAO colored film with protective and decorative effects.

[0003] There are many methods for coloring anodized aluminum films, but organic immersion coloring and electrolytic coloring with inorganic salts are currently the most widely used. Organic immersion coloring involves immersing the anodized aluminum film in a dye or dye precursor solution. The dye molecules are deposited and fixed in the pores of the anodized aluminum film through physical and chemical reactions, resulting in a rich, vibrant colored anodized aluminum film. However, the color stability and weather resistance of the colored anodized aluminum films produced by this method vary. Summary of the Invention

[0004] In view of the above problems, the present invention provides a colored aluminum anodized film and a preparation method thereof, which are used to solve the problems of color stability and weather resistance deviation of the current colored aluminum anodized film.

[0005] To achieve the above object, the technical solution adopted by the present invention is: A method for preparing a colored aluminum anodized film comprises the following steps: degreasing and removing oxide scale from an aluminum sheet, followed by electrochemical polishing to obtain a pretreated aluminum sheet, then anodizing the pretreated aluminum sheet to form an aluminum anodized film on the surface of the aluminum sheet, and finally immersing the aluminum anodized film in a diazonium salt solution and a mixed solution in sequence to obtain the colored aluminum anodized film; the electrolytic polishing solution used in the electrochemical polishing comprises water, thiourea, sulfonic acid-modified alendronic acid, and sulfuric acid; the electrolyte used in the anodizing comprises water, lactic acid, an electrolyte additive, and aluminum sulfate; the diazonium salt is 2-amino-5-ethylpyrazine diazonium salt; and the mixed solution contains terephthalic acid; the chemical structure of the sulfonic acid-modified alendronic acid is as follows: The chemical structure of the electrolyte additive is shown below: Preferably, in the electrolytic polishing solution, the mass fraction of thiourea is 1-3%, the mass fraction of sulfonic acid-modified alendronic acid is 15-30%, and the mass fraction of sulfuric acid is 10-20%.

[0006] Preferably, during the electrochemical polishing process, the temperature of the electrolytic polishing solution is controlled to be 35-45°C and the current density is controlled to be 0.3-0.5 A / cm 2 , the electrochemical polishing time is 4~7min.

[0007] Preferably, the preparation method of the sulfonic acid-modified alendronic acid is as follows: (4-amino-1-hydroxybutylidene)bisphosphonic acid and 4-(chlorosulfonyl)benzoyl chloride are mixed and reacted, and then mixed and reacted with water to obtain the sulfonic acid-modified alendronic acid; the molar ratio of the (4-amino-1-hydroxybutylidene)bisphosphonic acid and 4-(chlorosulfonyl)benzoyl chloride is 1:1.05~1.1.

[0008] Preferably, in the electrolyte used for the anodization, the concentration of lactic acid is 70-90 g / L, the concentration of the electrolyte additive is 40-60 g / L, and the concentration of aluminum sulfate is 15-25 g / L.

[0009] Preferably, during anodization, the electrolyte temperature is 25-35°C and the current density is 3-5 A / dm 2 , time is 45~60min.

[0010] Preferably, the preparation method of the electrolyte additive is as follows: allyl phosphoric acid and diisopropanolamine are mixed and reacted at 60~75°C for 8~10 hours to obtain an intermediate, and then the intermediate and bromocarboxylic acid are mixed and reacted at 70~75°C for 3~5 hours to obtain the electrolyte additive; the molar ratio of allyl phosphoric acid, diisopropanolamine and bromocarboxylic acid is 1.1~1.2:1:2~3; the bromocarboxylic acid is bromosuccinic acid.

[0011] Preferably, the preparation method of the diazonium salt solution is as follows: 2-amino-5-ethylpyrazine, hydrochloric acid and sodium nitrite aqueous solution are mixed and reacted at 0~5°C to obtain a diazonium salt solution; the mass ratio of 2-amino-5-ethylpyrazine and hydrochloric acid is 1:2~2.5, the mass fraction of hydrochloric acid is 16~18%, and the molar ratio of 2-amino-5-ethylpyrazine and sodium nitrite is 1:1.1~1.3.

[0012] Preferably, the preparation method of the mixed solution is as follows: mixing terephthalic acid, N,N-dimethylformamide and sodium carbonate to obtain a mixed solution; the molar ratio of terephthalic acid and sodium carbonate is 1:3~4, and the mass ratio of terephthalic acid and N,N-dimethylformamide is 1:5~7.

[0013] A colored anodized aluminum film is prepared by the method for preparing the colored anodized aluminum film as described above.

[0014] Compared with the prior art, the present invention has the following beneficial effects: The present invention is carried out electrochemical polishing, anodizing by aluminium flake successively, obtains aluminium anodic oxide film, then aluminium anodic oxide film is immersed in specific azo precursor solution, utilizes the azotization reaction between diazonium salt and benzene sulfonate, in the pore of porous oxide film, original position synthesizes red azo dye, completes the colouring to aluminium oxide film.The present invention is by synthesizing sulfonic acid modified alendronic acid, and itself and thiourea, sulfuric acid are compounded to form electrochemical polishing liquid, can effectively improve aluminium flake surface electrochemical polishing quality, reduce aluminium flake surface roughness, for subsequent formation uniform oxide film and uniform firm colouring provide good basis.In addition, the present invention has the electrolyte additive of phosphate group, carboxyl group and alcohol amino group simultaneously by synthesis, and the additive is compounded with lactic acid, can form the porous oxide film with better surface quality and suitable pore size, for the azo dye of subsequent original position synthesis fixes load in pore and provides good basis. Finally, the present invention can make the azo molecules well match the pore size of the porous membrane by screening azo precursors with specific structures, and use the sulfonic acid groups on the azo molecules to further improve the loading and fixation of the azo dye on the porous membrane, thereby obtaining an aluminum oxide film with good coloring effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 This is the H NMR spectrum of the sulfonic acid-modified alendronic acid prepared in Example 1 of the present invention; Figure 2 This is the H NMR spectrum of the electrolyte additive prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0016] In order to enable those skilled in the art to better understand the technical solution, the present invention is described in detail below in conjunction with embodiments. The description in this section is only exemplary and explanatory and should not have any limiting effect on the scope of protection of the present invention.

[0017] Example 1

[0018] The method for preparing the colored aluminum anodized film of this embodiment comprises the following steps: (1) The aluminum sheet is washed and degreased with a degreasing agent to obtain a degreased aluminum sheet; the degreasing agent is composed of water, sodium lauryl sulfate, and potassium phosphate, the concentration of sodium lauryl sulfate is 8 g / L, and the concentration of potassium phosphate is 50 g / L.

[0019] (2) Immerse the degreased aluminum sheet in a sodium hydroxide solution (mass fraction 35%) at a temperature of 50°C, take it out after 2 minutes, and rinse it with water until the pH of the washing solution is neutral to obtain the aluminum sheet after descaling.

[0020] (3) The aluminum sheet after descaling is electrochemically polished to obtain a pretreated aluminum sheet; the electrolytic polishing solution during electrochemical polishing consists of water, thiourea, sulfonic acid-modified alendronic acid and sulfuric acid, with the mass fraction of thiourea being 1%, the mass fraction of sulfonic acid-modified alendronic acid being 15%, and the mass fraction of sulfuric acid being 10%; during the electrochemical polishing process, the temperature of the electrolytic polishing solution is controlled at 35°C and the current density is 0.3A / cm 2 , the electrochemical polishing time is 4 minutes; the preparation method of sulfonic acid modified alendronic acid is as follows: (4-amino-1-hydroxybutylidene) bisphosphonic acid and dichloromethane are added to a stirring tank, stirred evenly, and a (4-amino-1-hydroxybutylidene) bisphosphonic acid solution with a mass fraction of 5% is obtained; 4-(chlorosulfonyl) benzoyl chloride and dichloromethane are added to a stirring tank, stirred evenly, and a 4-(chlorosulfonyl) benzoyl chloride solution with a mass fraction of 15% is obtained; the temperature of the (4-amino-1-hydroxybutylidene) bisphosphonic acid solution is adjusted to 0°C, and the 4-(chlorosulfonyl) benzoyl chloride solution is added dropwise to the (4-amino-1-hydroxybutylidene) bisphosphonic acid solution under stirring. After the addition is completed, triethylamine is added to the reaction system, and then the temperature is adjusted to room temperature. The reaction is continued with stirring for 5 hours, filtered, and the filtrate is distilled under reduced pressure to remove the solvent to obtain a concentrate. The concentrate is added to water (the mass of water is 1.2 times the mass of the concentrate), stirred for 8 hours, and distilled under reduced pressure again to remove water to obtain a crude product. Finally, the crude product is purified by column chromatography (the eluent is composed of petroleum ether, methanol and chloroform in a volume ratio of 8:2:1) to obtain sulfonic acid-modified alendronic acid; wherein the molar ratio of (4-amino-1-hydroxybutylidene) bisphosphonic acid, 4-(chlorosulfonyl) benzoyl chloride and triethylamine is 1:1.05:1.3, and the nuclear magnetic hydrogen spectrum of sulfonic acid-modified alendronic acid is as shown below. Figure 1 The chemical structure is shown below:

[0021] (4) Anodize the pretreated aluminum sheet to form an aluminum anodized film on the surface of the aluminum sheet; the electrolyte used in the anodizing process consists of water, lactic acid, electrolyte additives and aluminum sulfate, with the concentration of lactic acid being 70 g / L, the concentration of electrolyte additives being 40 g / L, and the concentration of aluminum sulfate being 15 g / L; during the anodizing process, the temperature of the electrolyte is 25°C, and the current density is 3 A / dm 2 , time is 45 minutes; Among them, the preparation method of the electrolyte additive is as follows: allyl phosphoric acid and acetonitrile are added to a stirring tank and stirred evenly to obtain an allyl phosphoric acid solution with a mass fraction of 18%, and then diisopropanolamine is added to the stirring tank, and the stirring tank is heated to stir the materials in the stirring tank at 60°C for 8 hours, and then cooled to room temperature. The liquid after the reaction is distilled under reduced pressure to remove the solvent to obtain an intermediate.

[0022] Then, the intermediate, bromocarboxylic acid and acetonitrile (the mass of acetonitrile is 80% of the mass of the intermediate) are added to a stirring tank and stirred evenly. The materials in the stirring tank are then heated to 80°C and stirred under reflux for 5 hours. The system after the reaction is then distilled under reduced pressure to remove acetonitrile to obtain a concentrate. Finally, the concentrate is purified by column chromatography to obtain an electrolyte additive; wherein the molar ratio of allyl phosphoric acid, diisopropanolamine and bromocarboxylic acid is 1.1:1:2, the bromocarboxylic acid is bromosuccinic acid, and the eluent for column chromatography purification is composed of petroleum ether, methanol and dichloromethane in a volume ratio. The nuclear magnetic hydrogen spectrum of the electrolyte additive is shown in FIG. Figure 2 The chemical structure is shown below:

[0023] (5) Add 2-amino-5-ethylpyrazine and hydrochloric acid into a stirred reactor, adjust the temperature of the material in the stirred reactor to 0°C, then add a sodium nitrite aqueous solution (mass fraction 20%), and stir to react for 3 hours to obtain a diazonium salt solution; wherein the mass ratio of 2-amino-5-ethylpyrazine to hydrochloric acid is 1:2, the mass fraction of hydrochloric acid is 16%, and the molar ratio of 2-amino-5-ethylpyrazine to sodium nitrite is 1:1.1.

[0024] Add terephthalic acid, N,N-dimethylformamide and sodium carbonate to a reactor and stir until the solids are fully dissolved to obtain a mixed solution; wherein the molar ratio of terephthalic acid to sodium carbonate is 1:3, and the mass ratio of terephthalic acid to N,N-dimethylformamide is 1:5.

[0025] (6) The aluminum sheet with an aluminum anodized film formed on the surface prepared in step (4) is immersed in the mixed solution prepared in step (5), subjected to ultrasonic dispersion treatment for 5 minutes, taken out and immersed in the diazonium salt solution prepared in step (5), soaked for 8 minutes and then taken out, the aluminum sheet is washed with deionized water, and a red colored oxide film is formed on the surface of the aluminum sheet after drying.

[0026] Example 2

[0027] The method for preparing the colored aluminum anodized film of this embodiment comprises the following steps: (1) The aluminum sheet is washed and degreased with a degreasing agent to obtain a degreased aluminum sheet; the degreasing agent is composed of water, sodium lauryl sulfate, and potassium phosphate, the concentration of sodium lauryl sulfate is 9 g / L, and the concentration of potassium phosphate is 55 g / L.

[0028] (2) Immerse the degreased aluminum sheet in a sodium hydroxide solution (mass fraction 40%) at a temperature of 55°C, take it out after 2 minutes, and rinse it with water until the pH of the washing solution is neutral to obtain the aluminum sheet after descaling.

[0029] (3) The aluminum sheet after descaling is electrochemically polished to obtain a pretreated aluminum sheet; the electrolytic polishing solution during electrochemical polishing consists of water, thiourea, sulfonic acid-modified alendronic acid and sulfuric acid, with the mass fraction of thiourea being 2%, the mass fraction of sulfonic acid-modified alendronic acid being 19%, and the mass fraction of sulfuric acid being 15%; during the electrochemical polishing process, the temperature of the electrolytic polishing solution is controlled at 40°C and the current density is 0.4A / cm 2 , the electrochemical polishing time is 6 minutes; the preparation method of sulfonic acid modified alendronic acid is as follows: (4-amino-1-hydroxybutylene) bisphosphoric acid and dichloromethane are added to a stirring tank, stirred evenly, and a (4-amino-1-hydroxybutylene) bisphosphoric acid solution with a mass fraction of 6% is obtained; 4-(chlorosulfonyl) benzoyl chloride and dichloromethane are added to a stirring tank, stirred evenly, and a 4-(chlorosulfonyl) benzoyl chloride solution with a mass fraction of 18% is obtained; the temperature of the (4-amino-1-hydroxybutylene) bisphosphoric acid solution is adjusted to 2°C, and the 4-(chlorosulfonyl) benzoyl chloride solution is added dropwise to the (4-amino-1-hydroxybutylene) bisphosphoric acid solution under stirring. After the addition is completed, triethylamine is added to the reaction system, and then the temperature is adjusted to room temperature. The reaction is continued with stirring for 6 hours, filtered, and the filtrate is distilled under reduced pressure to remove the solvent to obtain a concentrate. The concentrate is added to water (the mass of water is 1.3 times the mass of the concentrate), stirred for 9 hours, and distilled under reduced pressure again to remove water to obtain a crude product. Finally, the crude product is purified by column chromatography (the eluent is composed of petroleum ether, methanol, and chloroform in a volume ratio of 8:2:1) to obtain sulfonic acid-modified alendronic acid; wherein the molar ratio of (4-amino-1-hydroxybutylidene)bisphosphonic acid, 4-(chlorosulfonyl)benzoyl chloride, and triethylamine is 1:1.08:1.4. The chemical structure of the sulfonic acid-modified alendronic acid is shown below:

[0030] (4) Anodize the pretreated aluminum sheet to form an aluminum anodized film on the surface of the aluminum sheet; the electrolyte used in the anodizing process consists of water, lactic acid, electrolyte additives and aluminum sulfate, with the concentration of lactic acid being 80 g / L, the concentration of electrolyte additives being 50 g / L, and the concentration of aluminum sulfate being 20 g / L; during the anodizing process, the temperature of the electrolyte is 30°C, and the current density is 4 A / dm 2 , time is 50min; Among them, the preparation method of the electrolyte additive is as follows: allyl phosphoric acid and acetonitrile are added to a stirring tank and stirred evenly to obtain an allyl phosphoric acid solution with a mass fraction of 20%, and then diisopropanolamine is added to the stirring tank, and the stirring tank is heated to stir the materials in the stirring tank at 70°C for 9 hours, and then cooled to room temperature. The liquid after the reaction is distilled under reduced pressure to remove the solvent to obtain an intermediate.

[0031] The intermediate, bromocarboxylic acid, and acetonitrile (the mass of acetonitrile is 100% of the mass of the intermediate) are then added to a stirred tank and stirred evenly. The contents are then heated to 80°C and stirred under reflux for 5 hours. The reaction mixture is then distilled under reduced pressure to remove the acetonitrile, yielding a concentrate. The concentrate is then purified by column chromatography to yield an electrolyte additive. The molar ratio of allyl phosphoric acid, diisopropanolamine, and bromocarboxylic acid is 1.1:1:3, the bromocarboxylic acid is bromosuccinic acid, and the eluent for column chromatography purification is composed of petroleum ether, methanol, and dichloromethane in a volume ratio. The chemical structure of the electrolyte additive is shown below:

[0032] (5) Add 2-amino-5-ethylpyrazine and hydrochloric acid into a stirred reactor, adjust the temperature of the material in the stirred reactor to 2°C, then add a sodium nitrite aqueous solution (mass fraction of 22%), and stir to react for 3 hours to obtain a diazonium salt solution; wherein the mass ratio of 2-amino-5-ethylpyrazine to hydrochloric acid is 1:2.2, the mass fraction of hydrochloric acid is 17%, and the molar ratio of 2-amino-5-ethylpyrazine to sodium nitrite is 1:1.2.

[0033] Add terephthalic acid, N,N-dimethylformamide and sodium carbonate to a reactor and stir until the solids are fully dissolved to obtain a mixed solution; wherein the molar ratio of terephthalic acid to sodium carbonate is 1:3, and the mass ratio of terephthalic acid to N,N-dimethylformamide is 1:6.

[0034] (6) The aluminum sheet with an aluminum anodized film formed on the surface prepared in step (4) is immersed in the mixed solution prepared in step (5), subjected to ultrasonic dispersion treatment for 6 minutes, taken out and immersed in the diazonium salt solution prepared in step (5), soaked for 9 minutes and then taken out, and the aluminum sheet is washed with deionized water. After drying, a red colored oxide film is formed on the surface of the aluminum sheet.

[0035] Example 3

[0036] The method for preparing the colored aluminum anodized film of this embodiment comprises the following steps: (1) The aluminum sheet is washed and degreased with a degreasing agent to obtain a degreased aluminum sheet; the degreasing agent is composed of water, sodium lauryl sulfate, and potassium phosphate, the concentration of sodium lauryl sulfate is 10 g / L, and the concentration of potassium phosphate is 60 g / L.

[0037] (2) Immerse the degreased aluminum sheet in a sodium hydroxide solution (mass fraction 45%) at a temperature of 60°C, take it out after 3 minutes, and rinse it with water until the pH of the washing solution is neutral to obtain the aluminum sheet after descaling.

[0038] (3) The aluminum sheet after descaling is electrochemically polished to obtain a pretreated aluminum sheet; the electrolytic polishing solution during electrochemical polishing consists of water, thiourea, sulfonic acid-modified alendronic acid and sulfuric acid, with the mass fraction of thiourea being 3%, the mass fraction of sulfonic acid-modified alendronic acid being 30%, and the mass fraction of sulfuric acid being 20%; during the electrochemical polishing process, the temperature of the electrolytic polishing solution is controlled at 45°C and the current density is 0.5A / cm 2 , the electrochemical polishing time is 7 minutes; the preparation method of sulfonic acid modified alendronic acid is as follows: (4-amino-1-hydroxybutylidene) bisphosphoric acid and dichloromethane are added to a stirring tank, stirred evenly, and a (4-amino-1-hydroxybutylidene) bisphosphoric acid solution with a mass fraction of 8% is obtained; 4-(chlorosulfonyl) benzoyl chloride and dichloromethane are added to a stirring tank, stirred evenly, and a 4-(chlorosulfonyl) benzoyl chloride solution with a mass fraction of 20% is obtained; the temperature of the (4-amino-1-hydroxybutylidene) bisphosphoric acid solution is adjusted to 5°C, and the 4-(chlorosulfonyl) benzoyl chloride solution is added dropwise to the (4-amino-1-hydroxybutylidene) bisphosphoric acid solution under stirring. After the addition is completed, triethylamine is added to the reaction system, and then the temperature is adjusted to room temperature. The reaction is continued with stirring for 7 hours, filtered, and the filtrate is distilled under reduced pressure to remove the solvent to obtain a concentrate. The concentrate is added to water (the mass of water is 1.5 times the mass of the concentrate), stirred for 10 hours, and distilled under reduced pressure again to remove water to obtain a crude product. Finally, the crude product is purified by column chromatography (the eluent is composed of petroleum ether, methanol, and chloroform in a volume ratio of 8:2:1) to obtain sulfonic acid-modified alendronic acid; wherein the molar ratio of (4-amino-1-hydroxybutylidene)bisphosphonic acid, 4-(chlorosulfonyl)benzoyl chloride, and triethylamine is 1:1.1:1.5. The chemical structure of the sulfonic acid-modified alendronic acid is shown below:

[0039] (4) Anodize the pretreated aluminum sheet to form an aluminum anodized film on the surface of the aluminum sheet; the electrolyte used in the anodizing process consists of water, lactic acid, electrolyte additives and aluminum sulfate, with the concentration of lactic acid being 90 g / L, the concentration of electrolyte additives being 60 g / L, and the concentration of aluminum sulfate being 25 g / L; during the anodizing process, the temperature of the electrolyte is 35°C, and the current density is 5 A / dm 2 , time is 60min; The preparation method of the electrolyte additive is as follows: allyl phosphoric acid and acetonitrile are added to a stirring tank and stirred evenly to obtain an allyl phosphoric acid solution with a mass fraction of 24%, and then diisopropanolamine is added to the stirring tank, and the stirring tank is heated to stir the materials in the stirring tank at 75°C for 10 hours, and then cooled to room temperature. The liquid after the reaction is distilled under reduced pressure to remove the solvent to obtain an intermediate.

[0040] The intermediate, bromocarboxylic acid, and acetonitrile (the mass of acetonitrile is 120% of the mass of the intermediate) are then added to a stirred tank and stirred evenly. The contents are then heated to 80°C and stirred under reflux for 5 hours. The reaction mixture is then distilled under reduced pressure to remove the acetonitrile, yielding a concentrate. The concentrate is then purified by column chromatography to yield an electrolyte additive. The molar ratio of allyl phosphoric acid, diisopropanolamine, and bromocarboxylic acid is 1.2:1:3, the bromocarboxylic acid is bromosuccinic acid, and the eluent for column chromatography purification is composed of petroleum ether, methanol, and dichloromethane in a volume ratio. The chemical structure of the electrolyte additive is shown below:

[0041] (5) Add 2-amino-5-ethylpyrazine and hydrochloric acid into a stirred reactor, adjust the material temperature in the stirred reactor to 5°C, then add a sodium nitrite aqueous solution (mass fraction 25%), and stir and react for 4 hours to obtain a diazonium salt solution; wherein the mass ratio of 2-amino-5-ethylpyrazine to hydrochloric acid is 1:2.5, the mass fraction of hydrochloric acid is 18%, and the molar ratio of 2-amino-5-ethylpyrazine to sodium nitrite is 1:1.3.

[0042] Add terephthalic acid, N,N-dimethylformamide and sodium carbonate to a reactor and stir until the solids are fully dissolved to obtain a mixed solution; wherein the molar ratio of terephthalic acid to sodium carbonate is 1:4, and the mass ratio of terephthalic acid to N,N-dimethylformamide is 1:7.

[0043] (6) The aluminum sheet with an aluminum anodized film formed on the surface prepared in step (4) is immersed in the mixed solution prepared in step (5), subjected to ultrasonic dispersion treatment for 8 minutes, taken out and immersed in the diazonium salt solution prepared in step (5), soaked for 10 minutes and then taken out, and the aluminum sheet is washed with deionized water. After drying, a red colored oxide film is formed on the surface of the aluminum sheet.

[0044] Comparative Example 1 The difference between the preparation method of the colored anodized aluminum film of this comparative example and the preparation method of the colored anodized aluminum film of Example 1 is that in step (3) of the preparation method of the colored anodized aluminum film of this comparative example, the sulfonic acid-modified alendronic acid is replaced by benzenesulfonic acid and (4-amino-1-hydroxybutylene) diphosphoric acid in a molar ratio of 1:1.

[0045] Comparative Example 2 The difference between the preparation method of the colored anodized aluminum film of this comparative example and the preparation method of the colored anodized aluminum film of Example 1 is that sulfuric acid is replaced by nitric acid in step (3) of the preparation method of the colored anodized aluminum film of this comparative example.

[0046] Comparative Example 3 The difference between the preparation method of the colored anodized aluminum film of this comparative example and the preparation method of the colored anodized aluminum film of Example 1 is that thiourea is replaced by urea in step (3) of the preparation method of the colored anodized aluminum film of this comparative example.

[0047] Comparative Example 4 The difference between the preparation method of the colored aluminum anodized film of this comparative example and the preparation method of the colored aluminum anodized film of Example 1 is that diisopropanolamine is replaced by diethanolamine in the preparation method of the electrolyte additive in step (4) of the preparation method of the colored aluminum anodized film of this comparative example.

[0048] Comparative Example 5 The only difference between the preparation method of the colored aluminum anodized film of this comparative example and the preparation method of the colored aluminum anodized film of Example 1 is that the brominated carboxylic acid in the preparation method of the electrolyte additive in step (4) of the preparation method of the colored aluminum anodized film of this comparative example is bromomalonic acid.

[0049] Comparative Example 6 The only difference between the preparation method of the colored aluminum anodized film of this comparative example and the preparation method of the colored aluminum anodized film of Example 1 is that the bromocarboxylic acid in the preparation method of the electrolyte additive in step (4) of the preparation method of the colored aluminum anodized film of this comparative example is 2-bromobutyric acid.

[0050] Comparative Example 7 The difference between the preparation method of the colored aluminum anodized film of this comparative example and the preparation method of the colored aluminum anodized film of Example 1 is that in step (4) of the preparation method of the colored aluminum anodized film of this comparative example, the electrolyte additive is replaced with allyl phosphoric acid, diisopropanolamine and bromosuccinic acid in a molar ratio of 1:1:1.

[0051] Comparative Example 8 The difference between the preparation method of the colored aluminum anodized film of this comparative example and the preparation method of the colored aluminum anodized film of Example 1 is that in step (5) of the preparation method of the colored aluminum anodized film of this comparative example, 2-amino-5-ethylpyrazine is replaced by 2-amino-5-methylpyrazine.

[0052] Comparative Example 9 The difference between the preparation method of the colored anodized aluminum film of this comparative example and the preparation method of the colored anodized aluminum film of Example 1 is that in step (5) of the preparation method of the colored anodized aluminum film of this comparative example, 2-amino-5-ethylpyrazine is replaced by aminopyrazine.

[0053] Comparative Example 10 The difference between the preparation method of the colored anodized aluminum film of this comparative example and the preparation method of the colored anodized aluminum film of Example 1 is that in step (5) of the preparation method of the colored anodized aluminum film of this comparative example, terephthalic acid is replaced by isophthalic acid.

[0054] Comparative Example 11 The difference between the preparation method of the colored anodized aluminum film of this comparative example and the preparation method of the colored anodized aluminum film of Example 1 is that in step (5) of the preparation method of the colored anodized aluminum film of this comparative example, terephthalic acid is replaced by benzenesulfonic acid.

[0055] Experimental example To investigate the electrochemical polishing effectiveness of the electrolytic polishing solutions used in the Examples and Comparative Examples 1-3, the surface roughness of the pretreated aluminum sheets prepared in each of the Examples and Comparative Examples 1-3 was tested, and the surface appearance of the pretreated aluminum sheets was observed using a magnifying glass. The test results are shown in Table 1. Each sample was tested at five identical test points, and the average of the five test points was used as the final test result.

[0056] Table 1 Surface roughness and appearance of the pretreated aluminum sheets prepared in each embodiment and comparative examples 1-3

[0057] As shown in Table 1, the electrolytic polishing solutions used in Examples 1-3 of the present invention achieved superior electrolytic polishing results compared to Comparative Examples 1-3. The resulting pretreated aluminum sheets exhibited reduced surface roughness, providing a favorable foundation for subsequent formation of a uniform oxide film and consistent, durable coloring. The experimental results in Table 1 demonstrate that the sulfuric acid, sulfonic acid-modified alendronic acid, and thiourea in the electrolytic polishing solution exhibited a strong combined effect, and their simultaneous use significantly improved the surface quality of the aluminum sheet.

[0058] Effect Examples To examine the comprehensive performance of the colored oxide films prepared in each example and comparative example, the coloring effect of the colored oxide films in each example and comparative example was evaluated, the color of the colored oxide films in each example and comparative example was observed and recorded, and the color uniformity, salt spray resistance, and weather resistance of the colored oxide films in each example and comparative example were tested. The results are shown in Table 2. The color uniformity test method is as follows: 10 test points at the same location on each sample were selected, and the color difference ΔE between any two test points on each sample was measured using a colorimeter. The maximum color difference was recorded as the color uniformity test result for that sample. The salt spray resistance test method is as follows: The test sample was placed in a test chamber, and salt water containing 5% sodium chloride and a pH of 7 was sprayed through a spray device to allow the salt spray to settle on the test sample. The time when corrosion spots appeared on the sample surface was observed and recorded. The time when corrosion spots appeared on the sample surface was used as the salt spray resistance test result. The weather resistance test method is as follows: test samples are placed in an artificial UV aging chamber to simulate natural UV exposure. The color difference (ΔE) at the same location on the sample surface before and after the test for 3000 hours is observed and recorded. The color difference (ΔE) is used as the weather resistance test result. The comprehensive performance test results of the colored oxide films prepared in various examples and comparative examples are shown in Table 2.

[0059] Table 2 Comprehensive performance test results of the colored oxide films prepared in various examples and comparative examples

[0060] Note: “-” means not tested.

[0061] As shown in Table 2, the colored anodized aluminum films prepared by the present invention exhibit a bright red color, good color uniformity at different locations, and good salt spray resistance and weather resistance, showing promising application prospects. Furthermore, the test results in Table 1 indicate that the pretreated aluminum sheets prepared in Comparative Examples 1-4 have relatively high surface roughness and poor surface quality, which leads to poor quality of the subsequent oxide films. This, in turn, affects the in-situ formation and fixed loading of the azo dye in the pores of the oxide films, resulting in poor final coloring.

[0062] It can be seen from Example 1 and Comparative Examples 5-6 that after the bromocarboxylic acid is replaced by bromosuccinic acid with bromomalonic acid or 2-bromobutyric acid, the surface activity and acidity of the electrolyte additive are reduced due to the reduction in the number of carbon chains or the number of carboxyl groups, which in turn affects the formation quality of the oxide film and the pore size on the oxide film, resulting in a mismatch between the azo dye molecules and the pore size on the oxide film, resulting in a poor coloring effect.

[0063] It can be seen from Example 1 and Comparative Example 7 that after the electrolyte additive is replaced with a mixture of allyl phosphoric acid, diisopropanolamine and bromosuccinic acid in a molar ratio of 1:1:1, although the electrolyte contains active groups such as carboxyl, sulfonic acid and alcoholamine, the structural change of the substance causes the anodic oxidation process to change, thereby affecting the formation of the final porous oxide film and the coloring effect of the azo dye.

[0064] It can be seen from Example 1 and Comparative Example 8 that after replacing 2-amino-5-ethylpyrazine with 2-amino-5-methylpyrazine, the side chain carbon chain length of the pyrazine amino compound is reduced, resulting in the azo molecule being unable to be well embedded and fixed in the pores of the porous oxide film, thereby affecting the coloring effect.

[0065] It can be seen from Example 1 and Comparative Example 10 that after replacing terephthalic acid with isophthalic acid, the active sites of isophthalic acid are not unique, resulting in the synthesized azo dye having multiple structures, affecting the purity of the azo dye colored product, and further resulting in poor color uniformity of the colored oxide film.

[0066] It can be seen from Example 1 and Comparative Examples 9 and 11 that after replacing 2-amino-5-ethylpyrazine with aminopyrazine or replacing terephthalic acid with benzenesulfonic acid, due to the lack of side chains in the pyrazine amino compound or the small number of sulfonic acid groups in the synthesized azo molecule, the azo molecule does not match the pore structure of the porous oxide film or the azo molecule fixation effect is poor, and thus cannot be fixed and loaded in the pores of the porous oxide film, resulting in coloring failure.

[0067] It should be noted that, in this article, the terms: include, contain and any other variations are intended to cover non-exclusive inclusion, so that a process, method, article or device that includes a series of elements includes not only those elements, but also other elements that are not explicitly listed, or also includes elements that are inherent to such process, method, article or device. Specific examples are used herein to illustrate the principles and implementation methods of the technical solution of the present invention. The above examples are only used to help understand the method of the present invention and its core idea. The above is only a preferred embodiment of the present invention. It should be pointed out that due to the limitations of textual expression, there are objectively infinite specific structures. For ordinary technicians in this technical field, without departing from the principles of the present invention, several improvements, modifications or changes can be made, and the above technical features can be combined in an appropriate manner; these improvements, modifications, changes or combinations, or the direct application of the concept and technical solution of the present invention to other occasions without improvement, should be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a colored aluminum anodized film, characterized in that: The following steps are involved: The aluminum sheet is degreased and scaled, and then electrochemically polished to obtain a pretreated aluminum sheet. The pretreated aluminum sheet is then anodized to form an aluminum anodized film on the surface of the aluminum sheet. Finally, the aluminum anodized film is sequentially immersed in a diazonium salt solution and a mixed solution to obtain a colored aluminum anodized film. The electrolytic polishing solution used in the electrochemical polishing is composed of water, thiourea, sulfonic acid-modified alendronic acid and sulfuric acid. The electrolyte used in the anodizing is composed of water, lactic acid, an electrolyte additive and aluminum sulfate. The diazonium salt is 2-amino-5-ethylpyrazine diazonium salt. The mixed solution contains terephthalic acid. The chemical structure of the sulfonic acid-modified alendronic acid is shown below: The chemical structure of the electrolyte additive is shown below:

2. The method for preparing a colored anodized aluminum film according to claim 1, wherein: In the electrolytic polishing solution, the mass fraction of thiourea is 1-3%, the mass fraction of sulfonic acid-modified alendronic acid is 15-30%, and the mass fraction of sulfuric acid is 10-20%.

3. The method for preparing a colored anodized aluminum film according to claim 1 or 2, wherein: During electrochemical polishing, the temperature of the electrolytic polishing solution is controlled at 35~45℃ and the current density is 0.3~0.5A / cm 2 , the electrochemical polishing time is 4~7min.

4. The method for preparing a colored anodized aluminum film according to claim 1 or 2, characterized in that: The preparation method of the sulfonic acid-modified alendronic acid is as follows: (4-amino-1-hydroxybutylidene) bisphosphonic acid and 4-(chlorosulfonyl)benzoyl chloride are mixed and reacted, and then mixed and reacted with water to obtain the sulfonic acid-modified alendronic acid; the molar ratio of the (4-amino-1-hydroxybutylidene) bisphosphonic acid and 4-(chlorosulfonyl)benzoyl chloride is 1:1.05-1.

1.

5. The method for preparing a colored anodized aluminum film according to claim 1, wherein: In the electrolyte used for the anodization, the concentration of lactic acid is 70-90 g / L, the concentration of the electrolyte additive is 40-60 g / L, and the concentration of aluminum sulfate is 15-25 g / L.

6. The method for preparing a colored anodized aluminum film according to claim 1 or 5, characterized in that: During anodization, the electrolyte temperature is 25~35℃ and the current density is 3~5A / dm 2 , time is 45~60min.

7. The method for preparing a colored anodized aluminum film according to claim 1 or 5, characterized in that: The preparation method of the electrolyte additive is as follows: allyl phosphoric acid and diisopropanolamine are mixed and reacted at 60-75° C. for 8-10 hours to obtain an intermediate, and then the intermediate and bromocarboxylic acid are mixed and reacted at 70-75° C. for 3-5 hours to obtain the electrolyte additive; the molar ratio of the allyl phosphoric acid, diisopropanolamine and bromocarboxylic acid is 1.1-1.2:1:2-3; and the bromocarboxylic acid is bromosuccinic acid.

8. The method for preparing a colored anodized aluminum film according to claim 1, wherein: The preparation method of the diazonium salt solution is as follows: 2-amino-5-ethylpyrazine, hydrochloric acid and sodium nitrite aqueous solution are mixed and reacted at 0-5° C. to obtain a diazonium salt solution; the mass ratio of the 2-amino-5-ethylpyrazine and hydrochloric acid is 1:2-2.5, the mass fraction of the hydrochloric acid is 16-18%, and the molar ratio of the 2-amino-5-ethylpyrazine and sodium nitrite is 1:1.1-1.

3.

9. The method for preparing a colored anodized aluminum film according to claim 1, wherein: The mixed solution is prepared by mixing terephthalic acid, N,N-dimethylformamide and sodium carbonate to obtain a mixed solution; the molar ratio of terephthalic acid to sodium carbonate is 1:3-4, and the mass ratio of terephthalic acid to N,N-dimethylformamide is 1:5-7.

10. A colored anodized aluminum film prepared by the method for preparing a colored anodized aluminum film according to any one of claims 1 to 9.